10 Pre-clinical studies of sotagliflozin in hypertrophic cardiomyopathy - Rebecca Taichman; Benjamin Lee; Kenneth Margulies; Sharlene Day (Journal of Clinical and Translational Science, 2024)
OBJECTIVES/GOALS: Study the regulatory role of sodium glucose co-transporter 1 (SGLT1) in cardiomyocytes and the therapeutic potential of sotagliflozin in hypertrophic cardiomyopathy (HCM) by (a) quantifying SGLT1 expression in HCM and (b) examining the impact of sotagliflozin on cardiac mechanics. METHODS/STUDY POPULATION: * Use Western Blot in cardiac tissue from HCM and non-HCM patients and pre-existing RNA seq and proteomics datasets to quantify SGLT1 levels in HCM. Hypothesis: SGLT1 is upregulated in HCM * Determine how SGLT1/2 inhibition by sotagliflozin will affect cardiac mechanics using living myocardial slice (LMS) preparations. A vibratome creates 200um-thick slices from (a) failing HCM heart explants, (b) septal myectomy samples from HCM patients, and (c) nonfailing rejected donor hearts. LMS are mounted on a force transducer and work-loops are stimulated under varying pre- and after-loads. Collecting baseline and post-drug work loops allows each slice to function as its own control. Hypothesis: sotagliflozin will improve diastolic mechanics by reducing stiffness in the end-diastolic pressure-volume relationship RESULTS/ANTICIPATED RESULTS: * Preliminary results from RNA seq data indicate that SLC5A1 mRNA (encoding gene for SGLT1) is significantly decreased in HCM. No proteomics study examined thus far has detected SLC5A1, indicating that overall SGLT1 levels in cardiac tissue are quite low. We will examine SGLT1 levels in our own HCM and non-HCM tissue samples with both mass-spectrometry and Western Blot. * We analyze six slices from each heart and expect 15 donor hearts and 15 HCM hearts/myectomy samples. We visualize the work loop by plotting stress/strain. Stress/strain at mitral valve closure represents exponential end diastolic pressure-volume relationship; Stress/strain at aortic valve closure represents linear end systolic pressure volume relationship. A two-sample paired t-test will compare change in stiffness and elastance. DISCUSSION/SIGNIFICANCE: This project contributes to a growing body of research surrounding the currently unknown cardioprotective mechanism of SGLT 1/2 inhibitors, furthers the technique of using living myocardial slices to study cardiac mechanics, and supports a trial examining sotagliflozin in HCM, for which disease modifying therapy remains a prevailing unmet need.